Interleukin‐16 aggravates ovalbumin‐induced allergic inflammation by enhancing Th2 and Th17 cytokine production in a mouse model. Issue 3 (21st June 2019) - Li, Chunxia; Dai, Jun; Dong, Guanjun; Ma, Qun; Li, Zhihua; Zhang, Hui; Yan, Fenglian; Zhang, Junfeng; Wang, Bo; Shi, Hui; Zhu, Yuzhen; Yao, Xiaoying; et al.
Summary: Asthma is a chronic inflammatory disease that involves a variety of cytokines and cells. Interleukin‐16 (IL‐16) is highly expressed during allergic airway inflammation and is involved in its development. However, its specific mechanism of action remains unclear. In the present study, we used an animal model of ovalbumin (OVA)‐induced allergic asthma with mice harboring an IL‐16 gene deletion to investigate the role of this cytokine in asthma, in addition to its underlying mechanism. Increased IL‐16 expression was observed during OVA‐induced asthma in C57BL/6J mice. However, when OVA was used to induce asthma in IL‐16 −/− mice, a diminished inflammatory reaction, decreased bronchoalveolar lavage fluid (BALF) eosinophil numbers, and the suppression of OVA‐specific IgE levels in the serum and BALF were observed. The results also demonstrated decreased levels of T helper type 2 (Th2) and Th17 cytokines upon OVA‐induced asthma in IL‐16 −/− mice. Hence, we confirmed that IL‐16 enhances the lung allergic inflammatory response and suggest a mechanism possibly associated with the up‐regulation of IgE and the promotion of Th2 and Th17 cytokine production. This work explored the mechanism underlying the regulation of IL‐16 in asthma and provides a new target for the clinical treatment of asthma. Abstract : Interleukin‐16 (IL‐16) is highly expressed during allergic airway inflammation when OVA was used to induce asthma in IL‐16 −/− mice, a diminished inflammatory reaction, decreased bronchoalveolar lavage fluid (BALF) eosinophil numbers, the suppression of OVA‐specific IgE levels in the serum and BALF, and decreased levels of T helper type 2 (Th2) and Th17 cytokines were observed. Thus, we confirmed that IL‐16 enhances the lung allergic inflammatory response and suggest a mechanism possibly associated with the up‐regulation of IgE and the promotion of Th2 and Th17 cytokine production.